Highly efficient acrylic acid production from formaldehyde and acetic acid over the NASICON-type catalyst. Issue 11 (19th January 2023) - Gao, Qiliang; Zheng, Kaiwen; Li, Chao; Wang, Jiahao; Zhang, Guojie; Zhang, Qingde; Song, Faen; Zhang, Tao; Zhang, Junfeng; Han, Yizhuo
Abstract : NASICON material modulated by concomitantly-generated TiP2 O7 phase shows highly-efficient production of acrylic acid from formaldehyde and acetic acid. Abstract : The condensation of formaldehyde and acetic acid to acrylic acid (AA) is considered as one of the important routes for the clean and high value utilization of coal-based methanol derivatives. Herein, we successfully synthesized environment-friendly NASICON catalysts using Ti(SO4 )2 as the titanium source. With guaranteed high selectivity (∼78%), the space time yield of AA + MA (methyl acrylate) can be up to 123.9 μmol g −1 min −1, far higher than the results reported previously. Based on the characterizations, it is demonstrated that the modulation of the acidic and basic properties (including distribution, ratio of B/L, etc. ) led by the specific elemental and hybrid TiP2 O7 phase plays crucial roles in catalyst supremacy.